Perilaku Pencarian Informasi Peserta Didik Sekolah Dasar Negeri 48 Ganting Koto Tangah Padang - Oktaria, Putri; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
In this paper it is discussed about information searching attitude of elementary student in 48 Elementary school in Padang. This research is aimed to: (1) find out where the student of 48 Elementary school searching the source of information, (2) to know the kind of information searched by the student of 48 Elementary school. The data is gathered through observation and interview with the student in 48 Elementary school. Data analysis is conducted by grouping, tabulating and describing based on analyzing the data, it is concluded the following. First, students of 48 elementary school search the information in school library, book store, magazine and internet. Among the places above, most student get the information from internet and teacher. Second, the kind of information searched are: heroic article, news, book, story book and magazine. In this way, facilities as internet need to be completed, so that students can access the information quichly and efficienty. Keywords: Information searching; information searching attitude